A proposed personal growth program for teachers of Maryknoll College high school and an experimental study on group counseling for teachers - Reyes, Milagros R. (Animo Repository, 1975)
The first part of this study provides the high school teachers of Maryknoll College with a personal growth program as a part of the teachers' in-service training. To determine the needs of the teachers, interviews were conducted among the faculty members and administrators, observations were made, and evaluation reports on in-service seminars and workshops conducted in the high school in the past two years were assessed and summarized. This part of the study showed that there was a need for a personal growth program for the teachers and this program should use the group interaction approach in order to meet the needs of the teachers, and to suit the philosophy and objectives of the school. In the second part of the study, an experiment is conducted to determine whether or not group counseling would enhance the personal adjustment of the teachers. Furthermore, this part of the study aims to determine which of three treatment conditions, namely, group counseling, active control, and inactive control, would be more effective in enhancing the personal adjustment of the teachers. Design 2 or Randomized Control-group Pretest-Posttest Design (Van Dalen, 1973) was used in this study. The subjects were 24 female teachers from Maryknoll College High School (MCHS) in schoolyear 1974-75. Out of this total number, 8 belonged to the counseling group, 8 in the active control group, and 8 in the inactive control group. The measuring instrument used in this study was the Personal Orientation Inventory (POI) developed by Shostrom in 1966. The criterion measure for this study were 6 scales out of the 12 scales of the POI, namely: feeling reactivity, spontaneity, self-regard, self-acceptance, acceptance of aggression, and capacity for intimate contact. A summary of these scales made up the Personal Adjustment scale. An increase in the scale rating from pre-test condition to post-test condition was taken to mean as an enhancement of the personal adjustment of the subject. Findings of the study showed that while group counseling may be associated with increasing self-understanding and personal adjustment of teachers, it may not be justified as a dynamic basis of important changes in interpersonal adjustment. Psychotherapeutic approach in group counseling for teachers was worth experiencing not so much for its therapeutic value but more for the opportunity to learn experientially a process of personal problem solving as shown in the results of the subjective evaluation instrument. It was also concluded that psychotherapeutic approach in group counseling would not produce much changes among individuals, in this case, teachers, who may already be in the process of self-actualization. Group counseling with a psychotherapeutic orientation was not necessarily a superior treatment over some other group interaction approaches in enhancing personal adjustment when used with a normal adult population.